Illuminating Botteghe Oscure's British network. Issue 2 (11th May 2016) - Sullam, Sara
Abstract : Working at the intersection between literary history and periodical studies, this article investigates the role played by the literary journal Botteghe Oscure (Rome, 1948–1960) in processes of Anglo-Italian literary transfer. The article charts the journal's British network, analysing quantitatively the presence of both established and new writers. Further, it focuses on Botteghe Oscure 's publishing and distribution policy in the United Kingdom, drawing on its founder Marguerite Caetani's correspondence in order to interrogate the location of the journal within the Italian and the English literary systems, and thus illuminate the journal's role as a site of literary production as it was shaped in both Italy and Britain. Italian summary: Lavorando all'intersezione tra storia letterariae periodical studies il presente articolo indaga il ruolo svolto dalla rivista letteraria Botteghe Oscure (Roma 1948–1960) nei processi di transfer letterario anglo-italiano. Verrà dapprima delineata la rete britannica dei collaboratori della rivista, analizzando (e quantificando) la presenza di scrittori già affermati così come di nuovi entranti. In secondo luogo ci si soffermerà sulla pubblicazione e sulla distribuzione della rivista nel Regno Unito, così come si delinea nella corrispondenza di Marguerite Caetani (conservata presso la Fondazione Caetani di Roma) con gli editori. Ciò permetterà di interrogarsi sulla collocazione della rivista sia nel sistema letterario italiano sia in quello inglese e di illuminare così il suo ruolo come luogo di produzione culturale secondo le dinamiche proprie dei diversi contesti nazionali.